Thank you for smoking - Reitman, Jason, 1977-; Sacks, David O.; Eckhart, Aaron; Bello, Maria, 1967-; Bright, Cameron, 1993-; Brody, Adam, 1979-; Macy, William H., 1950-; Duvall, Robert; Buckley, Christopher, 1952-; Copyright Collection (Library of Congress) (United States : Fox Searchlight Pictures, 2006)
A tobacco industry lobbyist tries to promote cigarettes in a time when the health hazards of smoking have become too plain to ignore.The directorial debut from Jason Reitman, the media satire Thank You for Smoking stars Aaron Eckhart as Nick, a man who has turned spinning news and information into a successful career for the tobacco lobby. He plots strategies with his colleagues (Maria Bello and David Koechner) on how to make other dangerous products more appealing to the American public. Nick ends up going to Hollywood with his young son (Cameron Bright) in order to get a movie producer to include characters smoking in his newest film. Nick is kidnapped by a vigilante group concerned about the harmful nature of his product. The cast includes William H. Macy as a Senator who runs on a strong anti-tobacco position, Rob Lowe as the Hollywood bigwig, and Robert Duvall as the king of the tobacco industry. The film is an adaptation of the novel of the same name by Christopher Buckley.
Copyright: Twentieth Century Fox Film Corporation & Dune Entertainment, LLC. DCR 2006; PUB 19Jan06; REG 16Mar06; PA1-306-535.
Summary taken partially from Internet movie database.
Based on the novel of the same title by Christopher Buckley.
Not viewed.
Sources used: copyright data base; copyright data sheet; Internet movie database, Sept. 28, 2006; Variety, Sept. 9, 2005.
Executive producers, Peter Thiel, Elon Musk, Max Levchin, Mark Woolway, Edward R. Pressman, John Schmidt, Alessandro Camon, Michael Beugg ; camera, James Whitaker ; editor, Dana E. Glauberman ; music, Rolfe Kent ; production designer, Steve Saklad.
Keywords: Tobacco Industry; Adaptation -- Feature; Dark comedy -- Feature